CIRCULATING MICROPARTICLES, BLOOD CELLS, AND ENDOTHELIUM INDUCE PROCOAGULANT ACTIVITY IN SEPSIS THROUGH PHOSPHATIDYLSERINE EXPOSURE. Issue 3 (March 2016) - Zhang, Yan; Meng, Huan; Ma, Ruishuang; He, Zhangxiu; Wu, Xiaoming; Cao, Muhua; Yao, Zhipeng; Zhao, Lu; Li, Tao; Deng, Ruijuan; Dong, Zengxiang; Tian, Ye; et al.
Abstract : ABSTRACT: Sepsis is invariably accompanied by altered coagulation cascade; however, the precise role of phosphatidylserine (PS) in inflammation-associated coagulopathy in sepsis has not been well elucidated. We explored the possibility of exposed PS on microparticles (MPs), blood cells, as well as on endothelium, and defined its role in procoagulant activity (PCA) in sepsis. PS-positive MPs and cells were detected by flow cytometry, while PCA was assessed with clotting time, purified coagulation complex, and fibrin formation assays. Plasma levels of PS + MPs derived from platelets, leukocytes (including neutrophils, monocytes, and lymphocytes), erythrocytes, and endothelial cells were elevated by 1.49-, 1.60-, 2.93-, and 1.53-fold, respectively, in septic patients. Meanwhile, PS exposure on blood cells was markedly higher in septic patients than in controls. Additionally, we found that the endothelial cells (ECs) treated with septic serum in vitro exposed more PS than with healthy serum. Isolated MPs/blood cells from septic patients and cultured ECs treated with septic serum in vitro demonstrated significantly shortened coagulation time, greatly enhanced intrinsic/extrinsic FXa generation, and increased thrombin formation. Importantly, confocal imaging of MPs or septic serum-treated ECs identified binding sites for FVa and FXa to form prothrombinase, and further supported fibrin formation in the area where PS exposure was abundant. Pretreatment with lactadherin blocked PS on MPs/blood cells/ECs, prolonged coagulation time by at least 25%, reduced FXa/thrombin generation, and inhibited fibrin formation by approximately 85%. Our findings suggest a key role for PS exposed on MPs, blood cells, and endothelium in augmenting coagulation in sepsis. Therefore, therapies targeting PS may be of particular importance.